Comparative Studies of the Trace Elements Content of Some Herbal Tea Consumed in Jordan - Al-Dalain, Sati Y.A.; Abu-Darwish, Mohammad S.; Al-Fraihat, Ahmad H.; Al-Dabbas, Fawzi M.; Al-Dalin, Hammad K.; Al-Hamaidah, Khawla D. (Pakistan Journal of Nutrition, 2012)
Six mineral and trace elements (Cd, Ni, Pb, Cu, Mn and Zn) were determined in the five Samples of herbal teas commercially available in Jordanian Pharmaceutical market, such as Sahha Fennel Tea (SFT), Sahha Chamomile Tea (SCT), Sahha Herbal Tea (SHT), Miltea Herbal Tea (MHT) and Miltea Chamomile Tea (MCT). The mineral and trace elements content of the studied samples showed a wide variability. Mn was not detectable in SFT and SCT. It was ranged from 1.73 ppb in MCT to 5.95 ppb in SHT. The highest Cu content was 1.956 ppb in SCT and the lowest value was 0.939 ppb in SHT. However, it was not detectable in SFT, MHT and MCT. Cd ranged from 6.86 to 26.25 ppb in MCT and SHT respectively. Maximum concentration of Ni was 47.68 ppb in SHT while the minimum was 6.55 ppb in MCT. On the other hand, Zn concentration was not detectable in all studied samples. The results of this study indicated that, the herbal teas that are consumed in Jordan did not contain toxic elements.